Optimization of applied loads for assessing load-velocity relationship during back squat - Zhaoqian Li; Litong Xiao; Xing Zhang; Changda Lu; Junbei Bai (PLoS ONE, 2025)
Purpose This study aimed to identify the lightest load to validate the load-velocity (L-V) relationship in the back squat using the modified multiple-point (a lower highest load compared to the standard method) and in-field two-point methods. Methods Following the measurement of back squat one-repetition maximum (1RM), twenty college amateur athletes performed a multi-point incremental loads test (20%, 40%, 60%, 70%, 80%, and 90% 1RM), and five two-point tests (20%&90%, 20%&80%, 20%&70%, 20%&60%, and 20%&40% 1RM). The mean velocity (MV) of each submaximal load was collected to model the individual L-V relationship. Results The concurrent validity of the modified multiple-point method worked in incremental loads test until 70% and 80%1RM and for the in-field two-point method it only worked in 20%&90% 1RM conditions (−0.45 ≤ effect size ≤ 0.59; r ≥ 0.810). MV of heavy load in the in-field two-point method was higher than the standard method. Conclusion Modified multiple-point method assessing squat L-V relationship variables can choose the incremental load from 20% 1RM to 70%1RM (light load velocity at around 1.0 m/s and heavy load MV around 0.6 m/s) but in-filed two-point method should choose the lightest and heaviest load, around 20%1RM and 90%1RM (light load MV around 1.0 m/s and heavy load MV around 0.4 m/s).